Sciatic nerve injury: A simple and subtle model for investigating many aspects of nervous system damage and recovery - Savastano, Luis E. (2014)
Sciatic nerve injury has been used for over a century to investigate the process of nerve damage, to assess the absolute and relative capacity of the central and peripheral nervous systems to recover after axotomy, and to understand the development of chronic pain in many pathologies. Here we provide a historical review of the contributions of this experimental model to our current understanding of fundamental questions in the neurosciences, and an assessment of its continuing capacity to address these and future problems. We describe the different degrees of nerve injury - neurapraxia, axonotmesis, neurotmesis - together with the consequences of selective damage to the different functional and anatomic components of this nerve. The varied techniques used to model different degrees of nerve injury and their relationship to the development of neuropathic pain states are considered. We also provide a detailed anatomical description of the sciatic nerve from the spinal cord to the peripheral branches in the leg. A standardized protocol for carrying out sciatic nerve axotomy is proposed, with guides to assist in the accurate and reliable dissection of the peripheral and central branches of the nerve. Functional, histological, and biochemical criteria for the validation of the injury are described. Thus, this paper provides a review of the principal features of sciatic nerve injury, presents detailed neuroanatomical descriptions of the rat´s inferior limb and spine, compares different modes of injury, offers material for training purposes, and summarizes the immediate and longterm consequences of damage to the sciatic nerve.